2018
DOI: 10.4103/ijem.ijem_689_17
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal glycemic status of infants of diabetic mothers in a tertiary care hospital

Abstract: Background:Diabetes is a common medical complication during pregnancy that results in significant neonatal morbidities. In infants of diabetic mothers (IDMs), hypoglycemia is a common complication.Objective:To study the neonatal hypoglycemia in IDMs in a tertiary care hospital.Settings and Design:A cross-sectional study was done in postnatal ward in Bangladesh Institute of Research and Rehabilitation in Diabetic, Endocrine and Metabolic Disorders from January to December 2009.Subjects and Methods:The data of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
3
5
1
1
Order By: Relevance
“…Infants of diabetic mothers commonly experience hypoglycemia in the first hours after birth. However, the infants of diabetic mothers treated with diet did not have any association with hypoglycemia, while a significant increase in the frequency of hypoglycemia was observed in those born to mothers treated with insulin or oral agents (19,20). Our findings were in line with this result.…”
Section: Discussionsupporting
confidence: 89%
“…Infants of diabetic mothers commonly experience hypoglycemia in the first hours after birth. However, the infants of diabetic mothers treated with diet did not have any association with hypoglycemia, while a significant increase in the frequency of hypoglycemia was observed in those born to mothers treated with insulin or oral agents (19,20). Our findings were in line with this result.…”
Section: Discussionsupporting
confidence: 89%
“…On other hand Magadla Y et al 15 reported that the average maternal age was 33 years, with a range of 18-44 years. In the study of Begum S et al 13 reported that the majority mothers were between 21 and 40 years of age and mostly were multigravida, while in this study primiparous women were found in majority.…”
Section: Discussioncontrasting
confidence: 43%
“…In this study the frequency of neonatal hypoglycemia was observed among 24.8% of the cases. Similarly, Begum S et al 13 reported that the Hypoglycemia was observed among 38.3% infants of the diabetes mothers. However, Saqib M et al 14 observed lower rate of neonatal hypoglycemia as 14.8% among diabetes mothers.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Один из наиболее обсуждаемых вопросов -влияние терапии ГСД, получаемой во время беременности, на частоту гипогликемии новорожденного. Тогда как некоторые исследователи отмечают более высокую частоту гипогликемии у детей при применении инсулинотерапии во время беременности (по сравнению с таковой при использовании диеты или пероральных антидиабетических средств) [25,26], другие такую зависимость не выявляют [27]. Возможно, риск неонатальных осложнений обусловлен не характером терапии, а тем, что пациентки, имеющие потребность в инсулине, отличались более высоким «базовым» риском, прегестационным ожирением, чрезмерным ГУМТ и другими отягчающими факторами.…”
Section: акушерство и перинатологияunclassified